2021
DOI: 10.3390/ani11082184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Housing Systems during Suckling and Rearing Period on Skin and Tail Lesions, Tail Losses and Performance of Growing and Finishing Pigs

Abstract: Feasible alternatives to stressful weaning and tail-docking are needed to inhibit tail biting. Therefore, we investigated the effects of housing systems for 1106 pigs that were weaned from: (1) conventional farrowing crates (FC), (2) free-farrowing pens (FF), or (3) group housing of lactating sows (GH) into (1) conventional rearing pens (Conv) or (2) piglets remained in their farrowing pens for rearing (Reaf). Tails were docked or left undocked batchwise. All pigs were regrouped for the fattening period. Pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The values of β over the scoring days in REA are comparable with the course of tail lesions. A negative value at the beginning followed by one positive value at scoring day 3 showed an increase in tail lesions in the second week of REA, which was comparable to Lange et al [47]. The decrease on scoring day 4, also in the second week of REA, is in accordance with Honeck et al [48], who observed a comparable decrease in tail lesions in the second week after weaning and ascribed this to rank fighting at the beginning of REA.…”
Section: Rearingsupporting
confidence: 88%
“…The values of β over the scoring days in REA are comparable with the course of tail lesions. A negative value at the beginning followed by one positive value at scoring day 3 showed an increase in tail lesions in the second week of REA, which was comparable to Lange et al [47]. The decrease on scoring day 4, also in the second week of REA, is in accordance with Honeck et al [48], who observed a comparable decrease in tail lesions in the second week after weaning and ascribed this to rank fighting at the beginning of REA.…”
Section: Rearingsupporting
confidence: 88%
“…Grimberg-Henrici et al, 2019;, day 27 p.p. (Lange et al, 2021) or day 28 p.p. (Kutzer et al, 2009;de Ruyter et al, 2017;Greenwood et al, 2019), or to a 'long lactation' with weaning on for example day 34 p.p.…”
Section: Weaningmentioning
confidence: 99%